1989
DOI: 10.1016/0014-5793(89)80257-1
|View full text |Cite
|
Sign up to set email alerts
|

Level of protein kinase C activity correlates directly with resistance to adriamycin in murine fibrosarcoma cells

Abstract: In this report, we demonstrate a direct correlation between protein kinase C (PKC) activity and adriamycin (ADR) resistance in mouse fibrosarcoma cells. PKC activity was measured in four murine UV-2237M fibrosarcoma cell lines that differed in the degrees to which they expressed resistance to ADR, which is an inhibitor of PKC. A comparison of the four cell lines revealed a positive correlation between the level of PKC activity and resistance to ADR. Incubation of the cells with the PKC inhibitor H-7 produced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 12 publications
4
24
0
Order By: Relevance
“…This finding is to some extent reinforced by some observations showing that the level of PKC activity correlates with the degree of multidrug resistance to a specific drug (doxorubicin) as has been reported in a series of UV-2237M cell lines (O'Brian et al, 1989). We found the same in a series of KB cells selected in colchicine (Drew et al 1994).…”
Section: Pkc Activity In Mdr Cell Linessupporting
confidence: 86%
“…This finding is to some extent reinforced by some observations showing that the level of PKC activity correlates with the degree of multidrug resistance to a specific drug (doxorubicin) as has been reported in a series of UV-2237M cell lines (O'Brian et al, 1989). We found the same in a series of KB cells selected in colchicine (Drew et al 1994).…”
Section: Pkc Activity In Mdr Cell Linessupporting
confidence: 86%
“…In DOX-resistant HL-60 cells, a non-P-gp-expressing human promyelocytic leukaemia cell line, MRP was identified primarily in the endoplasmic reticulum, with lower levels also present in the plasma membrane (Marquardt and Center, 1992;Krishnamachary and Center, 1993), whereas a predominant function as a plasma membrane efflux pump has been demonstrated in a SCLC and in a non-small-cell lung carcinoma (NSCLC) cell line selected by exposure to DOX (Zaman et al, 1994 76(1), [67][68][69][70][71][72][73][74][75][76] In the present study, an additional possible mechanism for the intrinsically resistant phenotype of LoVo/C7 cells has been examined, namely alterations of PKC isoform pattern. Increases in overall PKC expression and/or activity have been demonstrated to correlate with a MDR phenotype in a number of cell lines O'Brian et al, 1989;Dong et al, 1991;Chaudary and Roninson, 1992;Gollapudi et al, 1992), with the Ca2+-dependent isoform oc-PKC specifically implicated in this phenomenon (Yu et al, 1991;Ahmad and Glazer, 1993). In a preliminary report, we analysed the role of Ca2+-dependent PKC isoforms in LoVo/C7 cells and our findings suggested a contribution of oc-PKC to the intrinsically resistant phenotype (Dolfini et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to overexpression of P-glycoprotein, other mechanisms also have been implicated to modulate MDR, including changes in transmembrane signalling pathways. Protein kinase C (PKC) activity has been shown to be elevated in a number of drugresistant cell types [5][6][7][8]. Other studies have shown that treatment of MDR cells with agents which alter PKC activity also altered the drug-resistant phenotype [5,6,9,10], further suggesting a role for PKC in multidrug resistance.…”
Section: Introductionmentioning
confidence: 99%